2009
DOI: 10.2355/isijinternational.49.881
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soluble Lubricant on Surface Imprinting in Temper Rolling by 4 Hi Rolling Mill

Abstract: Fig. 18. Models of imprinting of dull roll surface on mild steel sheet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Some of them are rolling speed, elongation, reduction ratio, properties of the material, roll parameters (roughness, radius, material, roughening method), lubrication conditions, etc. (Wu et al , 2019; Xia et al , 2017; Rodriguez-Vidal et al , 2020; Kijima, 2014; Mekicha et al , 2020; Nagase et al , 2009a; Köhler et al , 2016). Dick and Lenard (2005) concluded that as the rolling speed increased, loads and a forward slip would increase, thereby increasing the surface roughness of the sheets and approaching the value of the roll roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are rolling speed, elongation, reduction ratio, properties of the material, roll parameters (roughness, radius, material, roughening method), lubrication conditions, etc. (Wu et al , 2019; Xia et al , 2017; Rodriguez-Vidal et al , 2020; Kijima, 2014; Mekicha et al , 2020; Nagase et al , 2009a; Köhler et al , 2016). Dick and Lenard (2005) concluded that as the rolling speed increased, loads and a forward slip would increase, thereby increasing the surface roughness of the sheets and approaching the value of the roll roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Combining with practical production, Lee [8] , Sun [9,10] , and Zhang [11][12][13] et al researched that possible factors affect surface roughness of cold rolled products. Ma [14] and Nagase [15] et al investigated surface characteristic transfer (or imprinting) in cold rolling, showing the effect of rolling parameters, especially lubricating states. Recently, some researchers [2][3][4]16] have launched the preliminary study on surface roughness model of cold rolling, and given some simple surface roughness regression models.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Temper rolling experiments for as-annealed carbon steel strips have been performed using a 4-high rolling mill under dry condition. An electric-discharged dull roll and shot dull roll were employed as the work rolls.…”
Section: Introductionmentioning
confidence: 99%